Patients' preferences for adjuvant sorafenib after resection of renal cell carcinoma in the SORCE trial: what makes it worthwhile?. (21st November 2017) - Blinman, P L; Davis, I D; Martin, A; Troon, S; Sengupta, S; Hovey, E; Coskinas, X; Kaplan, R; Ritchie, A; Meade, A; Eisen, T; Stockler, M R
Abstract: Background: We sought to determine the survival benefits that patients judged sufficient to warrant adjuvant therapy with sorafenib for 1 year, or for 3 years after resection of renal cell carcinoma in the SORCE trial. Methods: SORCE participants from all sites in Australia and New Zealand, and selected sites in the UK, completed a validated preferences questionnaire at months 0, 3, 15, and 42 to elicit the minimum survival benefits they judged sufficient to warrant adjuvant sorafenib for 1 year (versus observation), or for 3 years (versus 1 year). The questionnaires used reference survival times of 5 and 15 years; and reference survival rates at 5 years of 65% and 85%. Results: The 233 participants had a median age of 57 years (range 29–78) and 71% were male. For 1 year of sorafenib versus no adjuvant therapy, the median benefits in survival times judged sufficient to warrant treatment were an extra 9 months beyond 5 years and an extra 1 year beyond 15 years; the median benefit in survival rates were an extra 4% beyond 65% and an extra 3% beyond 85% at 5 years. For 3 years of sorafenib versus 1 year of sorafenib, the median benefit in survival time judged sufficient to warrant extended treatment was an extra 1 year beyond both 5 and 15 years. Participants randomly allocated to treatment with sorafenib judged larger benefits necessary than those allocated to placebo. Participants' preferences were not associated with their baseline characteristics or the interval from randomisation. Conclusion: Most participants judged an extra year of survival necessary to warrant 1 year of adjuvant sorafenib worthwhile, and an additional year of survival to warrant extending the duration of sorafenib from 1 to 3 years. Patients' preferences are important in shared decision making. SORCE trial clinical trials number: NCT00492258.